Trends in the Risk to Wellbeing of a Community Population - Hyden, Deborah (International Journal of Population Data Science, 2018)
Background This paper reports on the work of a project resulting from the collaboration of Queens University Belfast and the North Down Community Network (NDCN). Although North Down has an affluent reputation, local knowledge within the NDCN indicates there may be pockets of deprivation related poor wellbeing. Objectives To identify areas of unmet need in a local context. Method Using data from the Northern Ireland Longitudinal Study (NILS) we adopted a multi-cohort approach to examine the links between household risk factors during childhood and physical/mental health to construct a predictive model of future health outcomes in the 46 super output areas (SOAs) of the North Down Area. Findings While preliminary results showed that the average probability for poor physical and mental health was likely to decline, two SOAs were likely to see an increase in poor physical health, one of which was also likely to witness an increase in poor mental health. Nonetheless, there were concerns regarding the magnitude of effect sizes between SOAs. Conclusions While results from this report may assist the NDCN to target areas in most need of resources to improve health and social care, lessons learned from this project are informative for future models of knowledge co-production intended to serve the public good.